2020
DOI: 10.1192/bjo.2020.102
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 deaths in people with intellectual disability in the UK and Ireland: descriptive study

Abstract: Background Rapid spread of coronavirus disease 2019 (COVID-19) has affected people with intellectual disability disproportionately. Existing data does not provide enough information to understand factors associated with increased deaths in those with intellectual disability. Establishing who is at high risk is important in developing prevention strategies, given risk factors or comorbidities in people with intellectual disability may be different to those in the general population. Aims … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
80
1
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(86 citation statements)
references
References 12 publications
1
80
1
4
Order By: Relevance
“…According to rank (with a cut off score 4), the enriched known or reported comorbid conditions or long-term complications are lupus erythematosus (Rank-1) [100], depressive disorder / mental depression (Rank-2) [30, 101], hepatitis C (Rank-3) [102], breast cancer (Rank-4) [75], arthritis (Rank-5) [103], asthma (Rank-6) [10, 77], liver cancer (Rank-6) [78], tuberculosis (Rank-7) [104, 105], diabetes (Rank-8) [82], myocardial infarction (Rank-9) [35, 106], macular degeneration (Rank-9) [80], chronic kidney disease (Rank-9) [56, 57], arteriosclerosis (Rank-10) [107], ulcerative colitis (Rank-10) [108], liver cirrhosis (Rank-11) [12, 109], sepsis / septicaemia /septic shock (Rank-11) [60, 81], other autoimmune diseases (Rank-12) [49, 50], cerebrovascular accident / stroke (Rank-13) [110], congenital anemia (Rank-13) [111], COPD (Rank-13) [86], multiple myeloma (Rank-14) [112], hypertensive disease (Rank-14) [9, 113], dyslipidemia (Rank-15) [93], metabolic syndrome X (Rank-15) [51, 114], osteoporosis (Rank-16) [91], prostate cancer (Rank-17) [115], psoriasis (Rank-17) [116], leukemia (Rank-18) [117, 118], long QT syndrome (Rank-18) [119], dementia (Rank-18) [120], schizophrenia (Rank-18) [121], intellectual disability (Rank-18) [122, 123], diabetic kidney disease/ diabetic nephropathy (Rank-18) [124]etc.…”
Section: Resultsmentioning
confidence: 99%
“…According to rank (with a cut off score 4), the enriched known or reported comorbid conditions or long-term complications are lupus erythematosus (Rank-1) [100], depressive disorder / mental depression (Rank-2) [30, 101], hepatitis C (Rank-3) [102], breast cancer (Rank-4) [75], arthritis (Rank-5) [103], asthma (Rank-6) [10, 77], liver cancer (Rank-6) [78], tuberculosis (Rank-7) [104, 105], diabetes (Rank-8) [82], myocardial infarction (Rank-9) [35, 106], macular degeneration (Rank-9) [80], chronic kidney disease (Rank-9) [56, 57], arteriosclerosis (Rank-10) [107], ulcerative colitis (Rank-10) [108], liver cirrhosis (Rank-11) [12, 109], sepsis / septicaemia /septic shock (Rank-11) [60, 81], other autoimmune diseases (Rank-12) [49, 50], cerebrovascular accident / stroke (Rank-13) [110], congenital anemia (Rank-13) [111], COPD (Rank-13) [86], multiple myeloma (Rank-14) [112], hypertensive disease (Rank-14) [9, 113], dyslipidemia (Rank-15) [93], metabolic syndrome X (Rank-15) [51, 114], osteoporosis (Rank-16) [91], prostate cancer (Rank-17) [115], psoriasis (Rank-17) [116], leukemia (Rank-18) [117, 118], long QT syndrome (Rank-18) [119], dementia (Rank-18) [120], schizophrenia (Rank-18) [121], intellectual disability (Rank-18) [122, 123], diabetic kidney disease/ diabetic nephropathy (Rank-18) [124]etc.…”
Section: Resultsmentioning
confidence: 99%
“…Higher mortality rate among people with learning disability has also been demonstrated in Wales 6 , New York State 7 , and the USA more broadly 3 . Not only are death rates higher for people with learning disability, but deaths occur at younger ages 3,8,9,22 . Indeed, the particularly elevated mortality rates among younger people with learning disability noted in our study have also been reported in the USA 3 .…”
Section: Discussionmentioning
confidence: 99%
“…There is also lack of clarity on the elevated risk of COVID-19 deaths among individuals with milder learning disability, and this needs exploration. 9 The higher risks of premature death among people with learning disability in England is wellknown, 1,10 and triggered the establishment of GP Learning Disability registers to allow for better provision of their healthcare. There are a number of mechanisms by which their risk of COVID-19 mortality may also be greater.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4,[12][13][14] Higher death rates from COVID-19 have been shown among groups with intellectual disability, possibly because people with intellectual disability having higher rates of medical conditions such as epilepsy, dysphagia and pneumonia. 15 Individuals from Black and minority ethnic backgrounds are more likely to have a poorer outcome in the event of infection. 16 Case fatality rates in individuals over 70 years of age range from 5 to 30%.…”
Section: Vulnerable Groups and Vulnerable Settingsmentioning
confidence: 99%